Importance of the 'crossover' concept in exercise metabolism - Brooks, G. A. (Clinical and Experimental Pharmacology and Physiology, 1997)
1. The 'crossover' concept is a model of substrate supply during exercise which makes the following predictions. 2. Lipid is the major fuel (approximately 60%) for non-contracting skeletal muscle and the body at rest. 3. Energy flux, as determined by exercise intensity, is the major factor in determining the balance of substrate utilization during exercise. Thus, moderate and greater exercise intensities increase contraction-induced muscle glycogenolysis and glycolysis, increase recruitment of fast-twitch muscle fibres, increase sympathetic nervous system activity and down-regulate mitochondrial fatty acid uptake. 4. Glycogen and glucose utilization scales exponentially to relative exercise power output with a greater gain in glycogen than in glucose use at high power. The relationship between free fatty acid flux and power output is an inverted hyperbola. Consequently, at high power outputs, the role of lipid oxidation is diminished. 5. Factors such as endurance training, energy supply, as influenced by dietary manipulation, and prior exercise play secondary roles in determining the balance of substrate utilization during exercise. 6. Comparisons of the metabolic responses in subjects engaged in activities requiring vastly different metabolic rates or comparisons of subjects of different gender, age or training status require normalization of data to total energy flux.